Sway Control of 3-Cars Crane System Using Proposed Fuzzy-PID Controller - Yildirim, Şahin; Gordebil, Aysegul (Recent Innovations in Mechatronics, 2020)
This paper presents a novel control approach for 3 cars crane systems. Nowadays; some problems for carrying unpredicted loads of crane systems exist. On the other hand; long bar loads are very important to carry without touch on other materials in factories. In this simulation study, fuzzy based controllers were designed to control vibrations of 3 cars crane system. The simulation results are improved and show this kind of controllers will be employed in real time such systems.